Evaluation and imaging of biodistribution of magnetic nanoparticles in a model of hepatic cirrhosis via alternating current biosusceptometry - Willmann, Raffael [UNESP] (2024)
In recent years, magnetic nanoparticles (MNPs) have exhibited theragnostic characteristics which confer a wide range of applications in the biomedical field. Consequently, through Alternating Current Biosusceptometry (ACB), magnetic nanoparticles can be used as tracers, allowing the study of healthy and cirrhotic livers and providing the ability to differentiate them through the reconstruction of quantitative images. The ACB system consists of a developing biomagnetic technique that has the ability to magnetize and measure the magnetic susceptibility of a material such as MNPs, thereby offering quantitative information about biological systems with magnetic tracers.